2014
DOI: 10.1186/1742-9994-11-12
|View full text |Cite
|
Sign up to set email alerts
|

Biological adhesion of the flatworm Macrostomum lignano relies on a duo-gland system and is mediated by a cell type-specific intermediate filament protein

Abstract: BackgroundFree-living flatworms, in both marine and freshwater environments, are able to adhere to and release from a substrate several times within a second. This reversible adhesion relies on adhesive organs comprised of three cell types: an adhesive gland cell, a releasing gland cell, and an anchor cell, which is a modified epidermal cell responsible for structural support. However, nothing is currently known about the molecules that are involved in this adhesion process.ResultsIn this study we present the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(94 citation statements)
references
References 72 publications
5
89
0
Order By: Relevance
“…However, an anterior-specific transcript might be a member of a larger gene family that exhibit a certain sequence overlap with other transcripts – resulting in cross-mapping of short reads. For example, in M. lignano , a tail-specific intermediate filament related transcript involved in adhesion was identified (Lengerer et al 2014). Intermediate filaments comprise a large protein family with various types and isoforms (eg keratin, desmin, vimentin, lamin, and neurofilaments), which results in a distribution of mapped reads within similar sequence regions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an anterior-specific transcript might be a member of a larger gene family that exhibit a certain sequence overlap with other transcripts – resulting in cross-mapping of short reads. For example, in M. lignano , a tail-specific intermediate filament related transcript involved in adhesion was identified (Lengerer et al 2014). Intermediate filaments comprise a large protein family with various types and isoforms (eg keratin, desmin, vimentin, lamin, and neurofilaments), which results in a distribution of mapped reads within similar sequence regions.…”
Section: Resultsmentioning
confidence: 99%
“…Differential transcriptomics permit the in silico subtraction of different samples yielding a quantitative ranking of differentially expressed transcripts. Based on a region-specific transcriptome of the flatworm Macrostomum lignano (Arbore et al 2015), an adhesion-related intermediate filament gene has been identified (Lengerer et al 2014) and potential glue candidates are currently under study (Ladurner, unpublished). Thus far, differential transcriptomic studies are becoming popular in bioadhesion research, primarily to identify candidate adhesive genes for reliable downstream analysis.…”
Section: Introductionmentioning
confidence: 99%
“…A 1 μg aliquot of total RNA was reverse transcribed using the 1st Strand cDNA Synthesis Kit for RT-PCR (AMV; Roche, Basel, Switzerland). Whole-mount in situ hybridisation was performed according to Lengerer et al (2014) with the following changes: (1) template DNA for producing DIG-labelled probe (501 bp) was made using Q5 High-Fidelity DNA polymerase (New England Biolabs, Ipswich, MA, USA) with the forward primer 5′-CAGTGCTCTGATCATCGATTCTTT-3′ and reverse primer 5′-TCTCTCATTTTGAAGCAATCTTCG-3′. A T7 promoter binding site was added to the reverse strand PCR primer and a Sp6 promoter binding site was added to the forward primer for negative control; (2) the heat fixation step at 80°C was omitted; and (3) colour development was performed in NBT/BCIP plus Suppressor 1-Step Solution (Thermo Fisher Scientific).…”
Section: Tensilin Expression and Localisation In Cuvierian Tubulesmentioning
confidence: 99%
“…Given its promise as a model for studying mechanisms governing pluripotency, a number of groups have worked to establish M. lignano as a model to study stem cell biology and regeneration (16,19,20), sexual selection and reproductive biology (21,22), bioadhesion (23), and neurobiology (24). Efforts of the M. lignano community have resulted in the development of a number of tools that can be used to study M. lignano biology (15,21,(25)(26)(27).…”
mentioning
confidence: 99%